Electrochemical Detection of Histamine in Red Wine Using CB[7] Modified Electrodes - Andisiwe Ngwekazi; Christopher Arendse; Priscilla Baker (ChemElectroChem)
Abstract In host‐guest chemistry, cucurbiturils are macrocyclic molecules made of glycoluril monomers linked by methylene bridges. This macrocyclic compound was applied in the design of electrochemical sensors for the detection of biogenic amines. Biogenic amines (BAs) are organic bases, which can be present in food and can cause several adverse reactions in consumers. The most significant BAs occurring in food are histamine, serotonin, and dopamine. Limited studies have been reported on thin film cucurbituril‐modified electrochemical sensors for solution‐based studies. An electrochemical sensor for the detection of biogenic amines was developed by immobilizing CB[7] at the surface of a glassy carbon electrode (GCE). Initially, the L‐lysine monomer was polymerized at the surface of GCE to introduce amine groups which will then form a peptide bond with CB[7]. Immobilization of CB[7] was performed through the electrodeposition method as well as physisorption with no applied potential to form GCE/PLL/CB[7]. Scanning electron microscopy and atomic force microscopy revealed morphological properties of CB[7] as reported in the literature. The response profile of the GCE/PLL/CB[7] sensor for histamine was studied using CV, SWV, and UV‐vis. The linear response was obtained in the range of 1.66×10−9–8.30×10−9 M for HI with a sensitivity of 255.22±38.20 uA M−1 cm−2. The proposed sensor was successfully applied to the determination of histamine in commercial red wine samples, with good recoveries.